2018
DOI: 10.1007/s10851-018-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Classic Photometric Stereo by Non-convex Variational Minimisation

Abstract: Estimating shape and appearance of a three dimensional object from a given set of images is a classic research topic that is still actively pursued. Among the various techniques available, photometric stereo is distinguished by the assumption that the underlying input images are taken from the same point of view but under different lighting conditions. The most common techniques provide the shape information in terms of surface normals. In this work, we instead propose to minimise a much more natural objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Such a simple least-squares approach may be replaced by robust variational or learning-based strategies to ensure robustness [13,17,33,34]. There also exist numerical solutions for handling non-Lambertian reflectance models [7,15,21,40], non-distant light sources [18,22,29,32], or the ill-posed cases where m = 2 [16,20,24,31] or m = 1 [5,8,39,45].…”
Section: Calibrated Photometric Stereo Under Directional Lightingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a simple least-squares approach may be replaced by robust variational or learning-based strategies to ensure robustness [13,17,33,34]. There also exist numerical solutions for handling non-Lambertian reflectance models [7,15,21,40], non-distant light sources [18,22,29,32], or the ill-posed cases where m = 2 [16,20,24,31] or m = 1 [5,8,39,45].…”
Section: Calibrated Photometric Stereo Under Directional Lightingmentioning
confidence: 99%
“…where i o (x) ∈ R 11 is the "orthographic integrability vector" containing factors c i, j u (x) and c i, j v (x), and a ∈ R 11 contain the minors A i, j k,l of A appearing in (34). Let us assume that there exist at least 11 points x ∈ Ω such that the matrix formed by concatenating row-wise the vectors i o (x) is full-rank (in practice, this property is satisfied as long as the surface is not trivial).…”
Section: Orthographic Casementioning
confidence: 99%
“…Despite its long history in computer vision [49,50], PS is still a fundamentally challenging research problem due to the unknown reflectance and global lighting effects of real-world objects [41]. For the sake of simplicity, the lighting positions and directions are often assumed to be known across the PS research community [4,28,38,48]. However, the real world applications of PS mostly deal with data represented by images acquired under unknown light conditions; see [5], [11], and [21].…”
Section: Introductionmentioning
confidence: 99%
“…Though in the research community, the position of the light sources is generally assumed to be known [9][10][11], real-world applications of PS often deal with datasets acquired under unknown light conditions [12,13]. In [14], Hayakawa has shown that the lighting directions can be identified directly from the data when at least six images with different illumination are available (see [14] and Section 2 for a proof), yielding the possibility to apply PS to field measurement scenarios, as in the case of archaeological excavations [15].…”
Section: Introductionmentioning
confidence: 99%